IDENTIFIKASI CENDAWAN YANG BERPOTENSI MENYEBABKAN PENYAKIT BUSUK KUNING PADA BATANG TANAMAN BUAH NAGA - Nova Kurniasari; Nur Annis Hidayati; Tri Wahyuni (EKOTONIA: Jurnal Penelitian Biologi, Botani, Zoologi, dan Mikrobiologi, 2019)
The attack of pathogenic fungi on dragon fruit plants in Penyak Village causes severe damage and shows symptoms of yellow rot on the trunk of dragon fruit. The research method used is exploration and identification. This study aims to explore fungi that have the potential to cause yellow rot based on the symptoms of yellow rot on the stems of dragon fruit plants in Penyak Village, Koba District, Central Bangka Regency. The results of 16 stem samples obtained 64 isolates and based on macroscopic and microscopic identification results of each isolate obtained seven genera namely Acremonium, Alternaria, Aspergillus, Cladosporium, Geotrichum, Fusarium, and Pestalotiopsis. The most common pathogenic fungi at mild symptoms are Pestalotiopsis, Alternaria, and Fusarium. Environmental factors (abiotic) such as soil moisture and air humidity that are high enough to affect the genus present, especially Fusarium.